Distance learning of Chinese throught the CLIL Approach: Students´ Perceptions of a Business Chinese Course during the COVID-19- Pandemic - GABBIANELLI, GLORIA (2026)
The present study aims at investigating students’ perceptions of their linguistic and cultural improvement in a CLIL-based Chinese business culture course attended by 15 Italian university students. An online teaching curriculum based on CLIL methodology consisting of six online lessons of Chinese culture has been proposed in the Teaching Chinese as a Foreign Language (TCFL) area. Data were collected through a perception questionnaire administrated at the end of course, based on a 5-point Likert-scale and consisting of 22 statements questions and three open questions. The questionnaire investigated students’ perceptions of teaching methodology and collaborative working, and their cultural and linguistic improvements. Results demonstrate that the students showed satisfactory attitude towards the effectiveness of the CLIL-based distance instruction in terms of perceived cultural and linguistic improvement. They also show the perceived effectiveness of CLIL technology-enhanced instruction for peer assessment activities and the use of online audiovisual resources.